2016
DOI: 10.1016/j.jtusci.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical studies for the determination of an antibiotic drug, d-cycloserine, in pharmaceutical and human biological samples

Abstract: An antibiotic drug, d-cycloserine (CYS), in phosphate buffer at different pH values was electrochemically studied using a gold electrode. A well-resolved, irreversible, diffusion-controlled voltammetric peak was obtained at 0.873 V in a pH 9.2 phosphate buffer solution with an ionic strength of 0.2 M. The experimental conditions, such as the solution pH and scan rate, were optimized. The pH dependence suggested that equal numbers of protons and electrons were involved in the electrochemical oxidation of CYS. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…The slope is near to half the theoretical value of 0.059 in equation ( 5), indicating that the ratio of y/n is very close to half." Thus, it can be concluded that two electrons and one proton were involved in the electron transfer which agrees with the mechanism previously reported for some structure similar compounds [63,64]. Scheme 1 represents the possible mechanism for anodic oxidative behavior of SLD, which can involve the oxidation of alkoxybenzene into quinone by undergoing a 2e,1H + oxidation as previously reported for Tamsulosin (TAM), another structurally similar compound [65,66].…”
Section: Effect Of Ph and Supporting Electrolytesupporting
confidence: 88%
“…The slope is near to half the theoretical value of 0.059 in equation ( 5), indicating that the ratio of y/n is very close to half." Thus, it can be concluded that two electrons and one proton were involved in the electron transfer which agrees with the mechanism previously reported for some structure similar compounds [63,64]. Scheme 1 represents the possible mechanism for anodic oxidative behavior of SLD, which can involve the oxidation of alkoxybenzene into quinone by undergoing a 2e,1H + oxidation as previously reported for Tamsulosin (TAM), another structurally similar compound [65,66].…”
Section: Effect Of Ph and Supporting Electrolytesupporting
confidence: 88%
“…Some working electrodes frequently used in voltammetric determinations are glassy carbon, graphite pencil, boron‐doped diamond, silver solid amalgam, silver, gold, carbon paste, bismuth electrodes, hanging mercury drop electrode (HMDE), etc. . Among these electrodes, HMDE has been used to determination of several inorganic and organic analytes.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, the design and methodology to obtain such systems have developed considerably. Different coating methods (e.g., cold spraying [9], dip coating [10], electrochemical methods [11], electrophoretic deposition [12], magnetron sputtering [13], photochemical oxidation [14], and matrixassisted pulsed laser evaporation (MAPLE) [15][16][17]) were applied for incorporating various antibiotics (e.g., gentamicin [18], vancomycin [19], tobramycin [20], rifampicin [21,22], or tetracycline hydrochloride [23,24]) onto bioactive surfaces.…”
Section: Introductionmentioning
confidence: 99%